A review of construction safety climate: Definitions, factors, relationship with safety behavior and research agenda. (October 2021) - Chen, Huihua; Li, Hujun; Goh, Yang Miang
Highlights: Recommends a set of definition and paradigms to facilitate future CSC research. Specified the different organizational levels of CSC. Proposed a set of CSC factors to ensure consistency in future studies. Summarised the key variables and pathways related to CSC and safety behavior. Identified four CSC research gaps for future research. Abstract: In recent years, numerous studies on construction safety climate (CSC) had emerged, but there are concerns about the inconsistencies in the definitions, measurement, and factor structures of CSC. The inconsistencies in these empirical studies cause difficulties in growing a coherent body of knowledge to facilitate its sustained development and implementation. Furthermore, because of the importance of construction worker safety behavior (CWSB), there is a need to further evaluate the relationship between CSC and CWSB, so that CSC can be effectively used to improve CWSB. Hence, this study aims to conduct a thorough review of previous studies on CSC to identify current research trends and gaps, provide a coherent theoretical framework and propose future research agenda. This paper first presents an overview of CSC research through analysis of publication years, affiliations, authors, researchers' collaborative networks, publication sources, and research topics. Subsequently, the study identified different definitions and conceptualization paradigms, and we recommend a perception-based definition focusing on safety management system as the object of perception. In addition, we distinguished different categories of CSC differentiated based on organizational levels. We reviewed established CSC scales and factor structures, but we realized that there were inconsistencies. Thus, we proposed a CSC factor structure using the validated items in past CSC scales. In addition, the review showed that the relationship between CSC and CWSB is mediated by different mediators, which are compiled in this paper to facilitate future studies. Finally, four CSC research areas were proposed based on the research gaps identified.